Effect of microtopography on osseointegration of implantable biomaterials and its modification strategies - Zhang, Yingying; Fan, Zhenmin; Xing, Yanghui; Jia, Shaowei; Mo, Zhongjun; Gong, He (Frontiers in Bioengineering and Biotechnology, 2022)
Orthopedic implants are widely used for the treatment of bone defects caused by injury, infection, tumor and congenital diseases. However, poor osseointegration and implant failures still occur frequently due to the lack of direct contact between the implant and the bone. In order to improve the biointegration of implants with the host bone, surface modification is of particular interest and requirement in the development of implant materials. Implant surfaces that mimic the inherent surface roughness and hydrophilicity of native bone have been shown to provide osteogenic cells with topographic cues to promote tissue regeneration and new bone formation. A growing number of studies have shown that cell attachment, proliferation and differentiation are sensitive to these implant surface microtopography. This review is to provide a summary of the latest science of surface modified bone implants, focusing on how surface microtopography modulates osteoblast differentiation in vitro and osseointegration in vivo, signaling pathways in the process and types of surface modifications. The aim is to systematically provide comprehensive reference information for better fabrication of orthopedic implants.